Is there a danger for myopia in anti-doping education? Comparative analysis of substance use and misuse in Olympic racket sports calls for a broader approach - Kondric, Miran (BioMed Central, 2011)
BACKGROUND: Racket sports are typically not associated with doping. Despite the common characteristics of being non-contact and mostly individual, racket sports differ in their physiological demands, which might be reflected in substance use and misuse (SUM). The aim of this study was to investigate SUM among Slovenian Olympic racket sport players in the context of educational, sociodemographic and sport-specific factors. METHODS: Elite athletes (N = 187; mean age = 22 ± 2.3; 64% male) representing one of the three racket sports, table tennis, badminton, and tennis, completed a paper-and-pencil questionnaire on substance use habits. Athletes in this sample had participated in at least one of the two most recent competitions at the highest national level and had no significant difference in competitive achievement or status within their sport. RESULTS: A significant proportion of athletes (46% for both sexes) reported using nutritional supplements. Between 10% and 24% of the studied males would use doping if the practice would help them achieve better results in competition and if it had no negative health consequences; a further 5% to 10% indicated potential doping behaviour regardless of potential health hazards. Females were generally less oriented toward SUM than their male counterparts with no significant differences between sports, except for badminton players. Substances that have no direct effect on sport performance (if timed carefully to avoid detrimental effects) are more commonly consumed (20% binge drink at least once a week and 18% report using opioids), whereas athletes avoid substances that can impair and threaten athletic achievement by decreasing physical capacities (e.g. cigarettes), violating anti-doping codes or potentially transgressing substance control laws (e.g. opiates and cannabinoids). Regarding doping issues, athletes' trust in their coaches and physicians is low. CONCLUSION: SUM in sports spreads beyond doping-prone sports and drugs that enhance athletic performance. Current anti-doping education, focusing exclusively on rules and fair play, creates an increasingly widening gap between sports and the athletes' lives outside of sports. To avoid myopia, anti-doping programmes should adopt a holistic approach to prevent substance use in sports for the sake of the athletes' health as much as for the integrity of sports.